2021
DOI: 10.4070/kcj.2020.0448
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Surgical Outcomes of Prosthetic and Native Valve Endocarditis

Abstract: Author's summary In the present study, the patterns and clinical outcomes of prosthetic valve endocarditis (PVE) surgery were analyzed as compared with native valve endocarditis (NVE). The proportion of PVE among surgical infective endocarditis increased gradually through the study period. Patients with PVE was characterized by old age and more extensive infective lesions. PVE group showed notably higher early and overall mortality, and valve reinfection as well. PVE carried significant perioperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Further, results of blood cultures can be inconclusive due to contamination by commensal bacteria, a complex polymicrobial biofilm (Oberbach et al, 2017), or insufficient amounts of bacteria to culture. Negative blood cultures are found in approximately 24% of all IE cases, which is similar for NVE (25%), CDRIE (26%), and PVE (23%) (Hussein et al, 2016;Koneru et al, 2018;Calais et al, 2019;de Camargo et al, 2019;El Gabry et al, 2019;Habib et al, 2019;Heriot et al, 2019;Nesterovics et al, 2019;Płońska-Gościniak et al, 2019;San et al, 2019;Witten et al, 2019;Bohbot et al, 2021;Duval et al, 2021;Jędrzejczyk-Patej et al, 2021;Michałowska et al, 2021;Pyo et al, 2021).…”
Section: Microbiological Diagnosismentioning
confidence: 79%
See 1 more Smart Citation
“…Further, results of blood cultures can be inconclusive due to contamination by commensal bacteria, a complex polymicrobial biofilm (Oberbach et al, 2017), or insufficient amounts of bacteria to culture. Negative blood cultures are found in approximately 24% of all IE cases, which is similar for NVE (25%), CDRIE (26%), and PVE (23%) (Hussein et al, 2016;Koneru et al, 2018;Calais et al, 2019;de Camargo et al, 2019;El Gabry et al, 2019;Habib et al, 2019;Heriot et al, 2019;Nesterovics et al, 2019;Płońska-Gościniak et al, 2019;San et al, 2019;Witten et al, 2019;Bohbot et al, 2021;Duval et al, 2021;Jędrzejczyk-Patej et al, 2021;Michałowska et al, 2021;Pyo et al, 2021).…”
Section: Microbiological Diagnosismentioning
confidence: 79%
“…Microorganism prevalence was evaluated based on all IE, NVE, CDRIE, PVE ( Figure 2 ). Staphylococcus aureus accounts for 27% of NVE, followed by streptococci (26%), and enterococci (12%) ( de Camargo et al, 2019 ; El Gabry et al, 2019 ; Habib et al, 2019 ; Heriot et al, 2019 ; San et al, 2019 ; Chambers and Bayer, 2020 ; Hubers et al, 2020 ; Bohbot et al, 2021 ; Duval et al, 2021 ; Pyo et al, 2021 ). Coagulase-negative staphylococci have a prevalence of 6.3% in NVE, which is in contrast to CDRIE with 25.2% ( Hussein et al, 2016 ; Koneru et al, 2018 ; Calais et al, 2019 ; Habib et al, 2019 ; Nesterovics et al, 2019 ; San et al, 2019 ; Witten et al, 2019 ; Bohbot et al, 2021 ; Duval et al, 2021 ; Pyo et al, 2021 ).…”
Section: Causative Microbesmentioning
confidence: 99%
“…The incidence of IE continues to increase and the mortality rate of IE has also remained at a high level (14–22% in hospital and 40% at 1 year after discharge) ( 12 , 13 ). In addition to the clinical characteristics of the patient and the presence of underlying cardiac disease, studies have shown that the prognosis of IE is also influenced by the type of causative microorganism, the location of the cardiac vegetation, and the type of valve involved (native valve or prosthetic valve) ( 9 , 14 ). It was found that among the pathogenic bacteria in IE, Staphylococcus aureus, Streptococcus griseus and Enterococcus are the most frequently seen in IE, accounting for about 70% of all ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…When compared to native valve endocarditis (NVE), prosthetic valve endocarditis (PVE) has a higher clinical death rate. PVE is also an independent risk factor for the prognosis of IE ( 14 ). The key to reducing the clinical mortality of IE patients is to immediately identify high-risk IE patients through comprehensive examination of early clinical characteristics, and then to use mature anti-infective medication therapy and suitable surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Korean Circulation Journal , Pyo et al 5) reported comparative surgical outcomes of PVE and native infective endocarditis (NVE). They concluded that PVE carried significant perioperative risks (the early mortality rates:14.3%), and was an independent risk factor of overall mortality.…”
mentioning
confidence: 99%